Relaciones interpersonales y clima laboral de los colaboradores en la empresa minera construcción y transporte La Libertad S.R.L. (MINCOTRALL) contrata de minera aurífera Retamas S.A. (MARSA) distrito de Parcoy - provincia de Pataz: 2016. - Romero Paz, Loyda (2016)
This thesis was performed with the purpose to explain the influence of interpersonal relations in the work environment of the collaborators in the mining company construction and transport the Freedom S.R.L. (MINCOTRALL) Contractual gold miner gorse S.A. (MARSA), District Of Parcoy - province Pataz: 2016. It has been considered to be the kind of applied research, taking as a basis an explanatory design, and the sample consisted of 193 collaborators, which were investigated by applying the methods and techniques of quantitative and qualitative investigation. The results obtained can be deduced that in this enterprise predominates low level of communication, inadequate interpersonal relations, low level of leadership and little teamwork which generate weak labor climate and consequently limit the work performance of the company. Finally we believe that the company through human resources area must implement training programs to improve interpersonal relationships and promote the leadership organizations and working in related equipment to generate a positive work climate in benefit of corporate profitability.